HUBUNGAN AKTIVITAS OLAHRAGA DENGAN KEJADIAN HIPERTENSI PADA KELOMPOK USIA 20-40 TAHUN DI DESA WILANAGARA TAHUN 2019 - Suryadi, Yadi (Kos Globalindo Group, 2021)
The problem in this study is that hypertension in Wilanegara village is very high. The formulation of the problem in this study is the extent of the relationship of sports activities with the incidence of hypertension in the age group of 20-40 years in Wilanagara Village in 2019 ?. The purpose of this study was to determine the relationship of sports activities with the incidence of hypertension in the age group of 20-40 years in Wilanagara Village in 2019. The method used in this study was descriptive correlational. The population in this study was hypertension sufferers in the age group of 20-40 years in Wilanagara Village in 2019, amounting to 528 people. Determination of the number of samples using the Slovin formula is a 10% significance level of 84 respondents. The selection of 84 respondents used a random sampling approach. Data processing techniques used are correlation test, simple linear regression test and hypothesis testing. The results of the validity of the variable X questionnaire score with variable Y showed 20 questionnaires declared valid. The reliability results showed that the X and Y variable questionnaires were stated to be reliable. Sports activity in the age group of 20-40 years in Wilanagara Village in 2019 has reached 76%, this is included in the high criteria. the incidence of hypertension in the 20-40 years age group in Wilanagara Village in 2019 has reached 32%, this is included in the low criteria. Based on the results of the calculation of the coefficient test results can be explained that the value of tcount> ttable, namely 4.188> 2.015 with a significance level of 0.008 <0.05, meaning that statistically Ha is accepted, meaning that there is a relationship between sports activity and the incidence of hypertension in the age group of 20-40 years in Wilanagara Village in 2019. The conclusion in this study is that there is a relationship between sports activities and the incidence of hypertension in the age group of 20-40 years in Wilanagara Village in 2019.